2015
DOI: 10.1037/abn0000039
|View full text |Cite
|
Sign up to set email alerts
|

Predicting psychosis across diagnostic boundaries: Behavioral and computational modeling evidence for impaired reinforcement learning in schizophrenia and bipolar disorder with a history of psychosis.

Abstract: There is increasing evidence that schizophrenia (SZ) and bipolar disorder (BD) share a number of cognitive, neurobiological, and genetic markers. Shared features may be most prevalent among SZ and BD with a history of psychosis. This study extended this literature by examining reinforcement learning (RL) performance in individuals with SZ (n = 29), BD with a history of psychosis (BD+; n = 24), BD without a history of psychosis (BD-; n = 23), and healthy controls (HC; n = 24). RL was assessed through a probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
(72 reference statements)
5
14
0
Order By: Relevance
“…Further, several recent reports examining reward-learning in SZ which also used paradigms that might engage cognitive control relatively more strongly have also failed to show correlations between task performance and negative symptoms. This is consistent with the hypothesis that the role of higher order cognitive processes in decision-making deficits may be somewhat independent of negative symptoms (Collins, et al, 2014; Culbreth, et al, 2015; Strauss, et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
“…Further, several recent reports examining reward-learning in SZ which also used paradigms that might engage cognitive control relatively more strongly have also failed to show correlations between task performance and negative symptoms. This is consistent with the hypothesis that the role of higher order cognitive processes in decision-making deficits may be somewhat independent of negative symptoms (Collins, et al, 2014; Culbreth, et al, 2015; Strauss, et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
“…Second, we examined language dysfunction and cognitive resources in SMI in a manner is that consistent with an RDoC approach (Insel et al, 2010). Our results of similar cognitive abilities and performance on the dual-task across our patient groups is consistent with previous findings (Barch, 2009; Barch and Sheffield, 2014; Simonsen et al, 2011; Strauss et al, 2015). While it is somewhat surprising that patients with schizophrenia did not differ in communication disturbances than patients without, it may be the case that patients with bipolar disorder and major depressive disorder who meet federal criteria for SMI–as in our study–exhibit similar communication disturbances as those with schizophrenia.…”
Section: Discussionsupporting
confidence: 93%
“…First, a broad array of deficits in attention, working memory, concentration and other “on-line” abilities is exhibited in individuals with SMI, and these deficits appear to be similar across SMI boundaries (Mackin and Areán, 2009; Simonsen et al, 2011; Strauss et al, 2015). Second, a number of correlational studies have observed that cognitive deficits are associated with more language impairment in schizophrenia, depression, and mania using behavioral-based procedures/technologies (Becker et al, 2012; Docherty, 2005; Radanovic et al, 2013; Rosenstein et al, 2014).…”
Section: 0 Introductionmentioning
confidence: 99%
“…In further contrast to some previous studies161920, we found no association of apathy symptoms with a relative preference for loss-avoidance learning or other learning parameters. However, other recent studies have also reported no relation of learning parameters with apathy symptom severity343738.…”
Section: Discussionmentioning
confidence: 82%